2014
DOI: 10.4103/1673-5374.131567
|View full text |Cite
|
Sign up to set email alerts
|

The potential of endogenous neurogenesis for brain repair and regeneration following traumatic brain injury

Abstract: Traumatic brain injury (TBI) is the leading cause of death and disability of persons under 45 years old in the United States, affecting over 1.5 million individuals each year. It had been thought that recovery from such injuries is severely limited due to the inability of the adult brain to replace damaged neurons. However, recent studies indicate that the mature mammalian central nervous system (CNS) has the potential to replenish damaged neurons by proliferation and neuronal differentiation of adult neural s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 62 publications
(65 reference statements)
1
34
0
Order By: Relevance
“…Following the cytokines' upregulation, cell adhesion molecules expressed on the surface of the cerebrovascular endothelium also increase. All of these processes eventually lead to the influx of inflammatory cells from the blood into the brain to initiate a host of restorative processes, including neurogenesis, synaptogenesis, oligodendrogenesis, and angiogenesis taking place in the brain as the spontaneous functional recovery after TBI [85][86][87][88][89][90]. Another factor of relevance is that the activation of microglial cells not only causes the amplification of the inflammatory response but also ROS production along with neurotoxic molecules.…”
Section: Neuroinflammationmentioning
confidence: 99%
“…Following the cytokines' upregulation, cell adhesion molecules expressed on the surface of the cerebrovascular endothelium also increase. All of these processes eventually lead to the influx of inflammatory cells from the blood into the brain to initiate a host of restorative processes, including neurogenesis, synaptogenesis, oligodendrogenesis, and angiogenesis taking place in the brain as the spontaneous functional recovery after TBI [85][86][87][88][89][90]. Another factor of relevance is that the activation of microglial cells not only causes the amplification of the inflammatory response but also ROS production along with neurotoxic molecules.…”
Section: Neuroinflammationmentioning
confidence: 99%
“…Elucidating which factors are involved, and how they interact with the SVZ niche in the developing, adult and ageing brain, will enhance our understanding of its underlying physiology, and how NSC homeostasis changes during the course of ageing. Moreover, unravelling the mechanisms underlying the regenerative potential, as well as NSC fate choice in pathophysiological conditions, is the key to understanding how NSCs can induce repair and regeneration in the adult brain …”
Section: Introductionmentioning
confidence: 99%
“…The aggregation of amyloid-b peptide (Ab) forming amyloid plaques is one of the pathological mechanisms of AD ( Joo et al, 2018;Lee et al, 2013;Yang et al, 2018;. The research on hippocampal neurogenesis of central nervous system (CNS) disorders, such as AD, stroke, traumatic brain injury, and so on, found that the endogenous neural stem cells (NSCs) may play regenerative and reparative roles (Sun, 2014;Yan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%